Valoración económica de disponibilidad del recurso hídrico y recreacional del Parque Nacional Natural Chingaza por medio de la metodología de transferencia de beneficios y costos de viaje (2020)
The Chingaza National Natural Park, home to one of the unique ecosystems in the Andean region, the páramo, has as a result of its location and proximity to the city of Bogotá, a great importance in the provision of water and recreational resources. This document summarizes its history, does a conceptual framework of the environmental importance of PNN Chingaza, and an analytical framework of two methodologies for the economic valuation of the park's water and tourism resources. Subsequently, these methodologies are applied to Chingaza PNN, where results show an availability to pay per individual of {dollar} 57,661 pesos for the recreational benefit, and a total of 35,233 million pesos annually for the use of water for human consumption. Finally, the benefits and limitations of the results are discussed and analyzed.